High-throughput sequencing reveals diverse oomycete communities in oligotrophic peat bog micro-habitat - Singer, David (2016)
Oomycete diversity has been generally underestimated, despite their ecological and economic importance. Surveying unexplored natural ecosystems with up-to-date molecular diversity tools can reveal the existence of unsuspected organisms. Here, we have explored the molecular diversity of five microhabitats located in five different oligotrophic peat bogs in the Jura Mountains using a high-throughput sequencing approach (Illumina HiSeq 2500). We found a total of 34 different phylotypes distributed in all major oomycete clades, and comprising sequences affiliated to both well-known phylotypes and members of undescribed, basal clades. Parasitic species, including obligate forms were well-represented, and phylotypes related to highly damaging invasive pathogens (Aphanomyces astaci: X1100 and Saprolegnia parasitica: X1602) were retrieved. Microhabitats differed significantly in their community composition, and many phylotypes were strongly affiliated to free water habitats (pools). Our approach proved effective in screening oomycete diversity in the studied habitat, and could be applied systematically to other environments and other fungal and fungal-like groups.